Faktor-Faktor yang Mempengaruhi Corporate Social Responsibility Disclosure (CSRD) di Indonesia: Meta Analisis - Susanto, Chyntia; Mulyani, Mulyani (E-Jurnal Akuntansi, 2023)
This study aims to examine the effect of profitability, firm size, leverage, board size, and institutional ownership on CSRD. The population of this research is research study articles published in 2018-2022 which examines the determinants of CSRD in companies listed on the Indonesia Stock Exchange for the 2013-2022 period. The research sample totaled 214 research study articles selected using a purposive sampling method. The analytical technique used to synthesize the sample is the Hunter & Schmidt meta-analysis method. The results of the study concluded that profitability, company size, leverage, board size, and institutional ownership proved to have a significant effect on CSRD. The results of this study support stakeholder theory, legitimacy theory, institutional theory, agency theory, and signaling theory regarding the factors that influence CSRD. Keywords: Meta Analysis; Corporate Social Responsibility Disclosure; Company Characteristics; Corporate Governance